Potential applications of natural origin polymer-based systems in soft tissue regeneration - Silva, Simone Santos (2010)
Despite the many advances in tissue engineering approaches, scientists still face significant challenges in trying to repair and replace soft tissues. Nature-inspired routes involving the creation of polymer-based systems of natural origins constitute an interesting alternative route to produce novel materials. The interest in these materials comes from the possibility of constructing multi-component systems that can be manipulated by composition allowing one to mimic the tissue environment required for the cellular regeneration of soft tissues. For this purpose, factors such as the design, choice, and compatibility of the polymers are considered to be key factors for successful strategies in soft tissue regeneration. More recently, polysaccharide-protein based systems have being increasingly studied and proposed for the treatment of soft tissues. The characteristics, properties, and compatibility of the resulting materials investigated in the last 10 years, as well as commercially available matrices or those currently under investigation are the subject matter of this review.